2010
DOI: 10.1007/s10555-010-9257-9
|View full text |Cite
|
Sign up to set email alerts
|

The guardians of the genome (p53, TA-p73, and TA-p63) are regulators of tumor suppressor miRNAs network

Abstract: The tumor suppressor p53 homologues, TA-p73, and p63 have been shown to function as tumor suppressors. However, how they function as tumor suppressors remains elusive. Here, I propose a number of tumor suppressor pathways that illustrate how the TA-p73 and p63 could function as negative regulators of invasion, metastasis, and cancer stem cells (CSCs) proliferation. Furthermore, I provide molecular insights into how TA-p73 and p63 could function as tumor suppressors. Remarkably, the guardians--p53, p73, and p63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 252 publications
(321 reference statements)
0
74
1
1
Order By: Relevance
“…miR-146a was up-regulated in TH1 cells throughout murine hematopoietic development (36). p53/TA-p73/p63 increased the expression of c-myc-suppressed miR-146a in B-cell lymphogenesis (37). This seems to contradict our results.…”
Section: Mir-155 and Mir-146a As Prognostic Biomarkers In Dlbcl Patiecontrasting
confidence: 92%
“…miR-146a was up-regulated in TH1 cells throughout murine hematopoietic development (36). p53/TA-p73/p63 increased the expression of c-myc-suppressed miR-146a in B-cell lymphogenesis (37). This seems to contradict our results.…”
Section: Mir-155 and Mir-146a As Prognostic Biomarkers In Dlbcl Patiecontrasting
confidence: 92%
“…5 Some of their target genes encode miRNAs instead of proteins. 6 These miRNAs have also been shown to play a role in controlling cell growth, apoptosis, senescence and autophagy in a p53-dependent fashion ( Table 1). [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recently, we identified miR-1246 as another novel p53 target miRNA.…”
Section: Mir-1246mentioning
confidence: 99%
“…Expression of P73 increased in oral squamous cell carcinoma compared to that in normal oral mucosa (27,28). Elevated expression of the P73 protein was found in oral precancerous lesions and squamous cell carcinoma (29,30), indicating that P73 expression was involved in the carcinogenesis from normal oral mucosa to precancerous lesions and squamous cell carcinoma. P73 expression was positively correlated to lymph node metastasis in oral squamous cell carcinoma (28)(29)(30), suggesting that tumors with high P73 expression were more invasive than those with low or no expression of P73.…”
Section: Discussionmentioning
confidence: 99%
“…Although P73 has been widely studied in many types of tumors, the P73 gene's function has not been clarified (29); in particular, P73 expression in malignant parotid gland tumors and its correlation with degree of malignancy have Studies showed that P73 arrested cell growth and induced apoptosis by activating the specific target genes of P53 and that different splicing isoforms of P53 and P73 activated distinct target genes. Therefore, P53 and P73 signaling pathways were partially overlapped (33).…”
Section: Discussionmentioning
confidence: 99%